2017
DOI: 10.1186/s12864-017-3561-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of direct HBx genomic targets

Abstract: BackgroundThe Hepatitis B Virus (HBV) HBx regulatory protein is required for HBV replication and involved in HBV-related carcinogenesis. HBx interacts with chromatin modifying enzymes and transcription factors to modulate histone post-translational modifications and to regulate viral cccDNA transcription and cellular gene expression. Aiming to identify genes and non-coding RNAs (ncRNAs) directly targeted by HBx, we performed a chromatin immunoprecipitation sequencing (ChIP-Seq) to analyse HBV recruitment on ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 61 publications
1
68
0
Order By: Relevance
“…Hence rather than on direct binding to damaged DNA an HBx-mediated HBV linkage to DNA repair could be based on Smc5/6 degradation yet also on other, additional cellular HBx targets [163]. …”
Section: Evidence For a Connection Between Hbv And The Host Dna Damentioning
confidence: 99%
“…Hence rather than on direct binding to damaged DNA an HBx-mediated HBV linkage to DNA repair could be based on Smc5/6 degradation yet also on other, additional cellular HBx targets [163]. …”
Section: Evidence For a Connection Between Hbv And The Host Dna Damentioning
confidence: 99%
“…Guerrieri et al 2017 identified and validated a role for HBx in regulating genes involved in endocytosis, predominantly members of the Ras-related in brain (Rab) family 9 . Anti-HBx chromatin immunoprecipitation studies identified HBx binding sites that included RAB1A, RAB2B and RAB5B promotors and none of the validated Rab genes were listed in our hypoxic gene set ( Supplementary Fig.1 ).…”
Section: Discussionmentioning
confidence: 97%
“…HBV was purified from a HepAD38 producer line as previously reported 57 . Briefly, virus was purified using centrifugal filter devices (Centricon Plus-70 and Biomax 100.000, Millipore Corp., Bedford, MA) and stocks with a titre between 3×10 9 and 3×10 10 viral genome equivalents (vge) per mL stored at −80°C. HBV-X-virus was purified from a HepG2 based cell line containing a HBV 1.3x overlength integrated viral genome where both 5’ and 3’ HBx genes were knocked out by a point mutation that changes the eight amino acid to a stop codon (CAA-to-TAA) as previously described 44 .…”
Section: Methodsmentioning
confidence: 99%
“…Aberrant regulation of miR-15b in human cancers reportedly has an important role in cancer development, contributing to reduced proliferation, cell death, angiogenesis and metabolic reprogramming and metastasis resistance, as well as tumor-associated inflammation and genomic instability (37). miR-576 is directly targeted by hepatitis B virus-encoded X protein (38). miR-155 and miR-500 were reported as potential markers of aflatoxin exposure (39), which suggests that miRs may be used as potential biomarkers for the diagnosis of LTBI.…”
Section: Discussionmentioning
confidence: 99%